Is the human movement effect stable over time? The effects of presentation format on acquisition and retention of a motor skill. (23rd August 2021) - H'mida, Cyrine; Kalyuga, Slava; Souissi, Nafaa; Rekik, Ghazi; Jarraya, Mohamed; Khacharem, Aïmen
Abstract: Objectives: The aim of the current study was to investigate the robustness of the human movement effect and its stability over time by comparing the effectiveness of dynamic and static presentations on acquisition and retention of a gross motor skill. Methods: One hundred and seven first‐year students studying for the certificate in Physical Education course were randomly divided into three groups: (i) static pictures ( N = 32), (ii) enriched static pictures with arrows ( N = 34), and (iii) video ( N = 41). They were instructed to observe the demonstration of the Ippon‐Seoi‐Nage (a Judo technique) and reproduce it during the acquisition phase or after a delay of 1 week during the retention phase. Results and Conclusions: The results showed that enriched static pictures (with arrows) resulted in more efficient learning than the static pictures (without arrows). Most importantly, it was shown that learners receiving the video presentation outperformed learners receiving the static presentations, with regard to acquisition and retention, indicating therefore a robust human movement effect. Implications: These findings provide confirmation of the superiority of video presentations for teaching and learning motor skills involving the entire human body. Lay Description: What is already known about this topic: External visualizations are broadly used in Physical education (PE) and sport context. Static visualizations are regarded as the fundamental tools used by PE teachers to communicate visual information that is difficult to verbally describe. Increasing use of dynamic visualizations such as videos largely supplanted the use of static pictures in PE context What this paper adds: Comparing the effectiveness of static pictures and digital videos in tactical learning Exploring the human movement effect and its stability over time Implications for practice and/or policy: The human movement effect is a robust phenomenon not only when it is evaluated immediately after the learning phase but also after a notable delay. Dynamic visualizations remain the most powerful computer‐based technique by which people can learn complex motor skills.